2012
DOI: 10.1021/es302306b
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic Improvements in Beach Water Quality Following Gull Removal

Abstract: Gulls are often cited as important contributors of fecal contamination to surface waters, and some recreational beaches have used gull control measures to improve microbial water quality. In this study, gulls were chased from a Lake Michigan beach using specially trained dogs, and water quality improvements were quantified. Fecal indicator bacteria and potentially pathogenic bacteria were measured before and during gull control using culture methods and quantitative polymerase chain reaction (qPCR). Harassment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
75
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(84 citation statements)
references
References 38 publications
(75 reference statements)
4
75
3
Order By: Relevance
“…Evidence of gull contamination in water was widespread at all beaches, consistent with previous reports in marine regions (31,40), with the Gull2 marker detected in 83% of samples with high E. coli levels and 82% of samples with low E. coli levels. Traditional FIB concentrations in gull feces have been reported to be highly varied, with concentrations of E. coli and enterococci reported to range between 10 2 and 10 8 CFU/g (41) and between 10 2 and 10 10 CFU/g (42-44), respectively.…”
Section: Discussionsupporting
confidence: 91%
“…Evidence of gull contamination in water was widespread at all beaches, consistent with previous reports in marine regions (31,40), with the Gull2 marker detected in 83% of samples with high E. coli levels and 82% of samples with low E. coli levels. Traditional FIB concentrations in gull feces have been reported to be highly varied, with concentrations of E. coli and enterococci reported to range between 10 2 and 10 8 CFU/g (41) and between 10 2 and 10 10 CFU/g (42-44), respectively.…”
Section: Discussionsupporting
confidence: 91%
“…For instance, the occurrence of STEC and EPEC has been previously found in some wild birds in Europe, Japan, and the United States, but these studies were limited to only gull and pigeon (15)(16)(17)(18)(19)(20)(21). Moreover, the contribution of fecal bacteria from avian sources and subsequent deterioration of water quality have been demonstrated in a number of studies (22,23), which found a significant correlation between the number of birds and the E. coli concentration (24,25). A direct link between avian STEC isolates causing human illness has also been reported (26).…”
mentioning
confidence: 99%
“…Microbial source tracking (MST) methodology offers tools to diagnose and identify fecal contamination sources in the environment (1,2). Although it is not a standard environmental monitoring method used for routine regulatory purposes, it has been extensively studied and applied worldwide, especially for deciphering fecal pollution in surface and recreational waters (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14).…”
mentioning
confidence: 99%